APPLICATION OF DEMONSTRATION METHOD IN LEARNING MAHARAH KALAM IN THE DARUSSALAM SCHOOL LAWANG MALANG: Penerapan Metode Demonstrasi Dalam Pembelajaran Maharah Kalam di Sekolah SMA Darussalam Lawang Malang - Akhmad Zainur Roziqin; Khizanatul Hikmah (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This thesis discusses the Application of Demonstration Methods in Learning Maharah Kalam in the Darussalam School Lawang Malang. In learning Maharah kalam rarely used by the teacher when learning then learning is given classic and does not vary, many students do not know the benefits of maharah kalam and are not confident in speaking Arabic. With this the researchers implemented a new program, The Demonstration Method.This research methodology uses a qualitative approach. The research data collection was obtained by participatory observation techniques, interviews, and document studies. Analysis of the data of this study was obtained using data reduction techniques, data presentation, and drawing conclusions.The results of the study revealed the findings that Application of Demonstration Method in Learning Maharah Kalam in the Darussalam School Lawang Malang was as follows: 1) Learning the Arabic Club Program was carried out through 3 learning activities, namely: Arabic dialogue, Arabic games, and Arabic